Pengaruh Pendidikan Madrasah Diniyyah Terhadap Prestasi Belajar Mata Pelajaran Aqidah Akhlak: Studi Kasus : Peserta Didik Kelas IX MTs PPAI Darun Najah Ngijo Karangploso Malang - Wardani, Dian Kusuma; Mujahid, Ahmad Syafiq (JoEMS (Journal of Education and Management Studies), 2023)
ABSTRACT The purpose of this study was to determine the effect of madrasah diniyah education on learning achievement of aqidah morals in class IX students at Madrasah Tsanawiyah PPAI Darun Najah Malang. The type of quantitative research used in this research is data collection techniques using questionnaires and documentation. The subjects of this study were 26 students of class IX Ngijo Karangploso Malang. Collecting data using a questionnaire instrument, namely the questionnaire method. The results of this study found that there was an influence of madrasah diniyah on the achievement of aqidah morals of Asymp. Sig (2-tailed) 0.000 < (alpha) 0.05. So it can be said that there is an influence of madrasah diniyah education on learning achievement of ahlaq aqidah in class IX students of Madrasah Tsanawiyah PPAI Darun Najah Ngijo Karangploso Malang.